1989
DOI: 10.1097/00132586-198910000-00033
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Abdominal Operations in the Patient with Acquired Immunodeficiency Syndrome

Abstract: \s=b\We have reviewed the medical records of ten patients with acquired immunodeficiency syndrome who required emergency celiotomy in a three-year period. These

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
1
5
1
Order By: Relevance
“…The overall morbidity (49%) and mortality (37%) rates for HIV-infected individuals in the present series is comparable to most reports. [1][2][3]9,10 In fact, our rates mirror the published experience of 13 series of laparotomies in patients infected with HIV, which show a complication rate of 46% and a death rate of 30%. 4 Mortality in our study was related to an ongoing septic process, AIDS-related pathologic conditions at laparotomy, and blood product transfusions.…”
Section: Commentsupporting
confidence: 77%
See 1 more Smart Citation
“…The overall morbidity (49%) and mortality (37%) rates for HIV-infected individuals in the present series is comparable to most reports. [1][2][3]9,10 In fact, our rates mirror the published experience of 13 series of laparotomies in patients infected with HIV, which show a complication rate of 46% and a death rate of 30%. 4 Mortality in our study was related to an ongoing septic process, AIDS-related pathologic conditions at laparotomy, and blood product transfusions.…”
Section: Commentsupporting
confidence: 77%
“…Early reports of abdominal surgery in patients with AIDS described perioperative mortality of 50%. [1][2][3] A more recent report indicates a perioperative mortality of 12% in a series of patients with AIDS undergoing emergent laparotomy. 4 In that study, worse prognoses were found with a lack of ongoing prophylactic treatment for AIDS-related disease, active opportunistic infections, Walter Reed VI classification, 5 and ongoing sepsis at the time of operation.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 High mortality and morbidity rates had been reported in various studies on abdominal surgery in HIV-infected patients. 6 Our mortality rate of 7% (6 out of 85) is much lower than reported rates of 19% to 48% in AIDS patients. Acceptable morbidity and mortality rates are achievable in this immunocompromised group as we see in normal patients.…”
Section: Discussioncontrasting
confidence: 51%
“…Since the initial descriptions of HIV and AIDS-defining illnesses, many reports have validated the safety of abdominal surgery in the HIV/AIDS patient. (1)(2)(3)(4)(5)(6)(7)(8) Immune status has been implicated as a marker of potential outcome in patients with HIV/AIDS. The introduction ofhighly active antiretroviral therapy (HAART) in the mid-1990s heralded a new era in the treatment of HIV/AIDS.The impact of HAART on surgical outcomes has beenshown to be protective in some series (9) but without overall improvement in others.…”
Section: Introductionmentioning
confidence: 99%
“…4,18 Figure 2 shows the most frequently performed emergency operations in AIDS patients. 9, 16,17,[19][20][21][22] Emergency operations usually are required for AIDS-related complications, but non-AIDS-related conditions (eg, acute appendicitis) may develop and be masqueraded by underlying AIDS symptomatology.…”
Section: Indications For Operationmentioning
confidence: 99%